Outcome with surgical treatment of canine soft tissue sarcoma in the region of the ischiatic tuberosity: A veterinary society of surgical oncology retrospective study. (25th April 2022) - Paulos, Patrisha E.; Boston, Sarah; Skinner, Owen T.; Liptak, Julius M.; Amsellem, Pierre M.; Fournier, Quentin; Wood, Christopher J.; Annoni, Maurizio; Murgia, Daniela; Oblak, Michelle L.; Dean, Barnaby L.; Baird, Steven D.; et al.
Abstract: The aim of this study was to determine the outcome of dogs with soft tissue sarcoma (STS) within the region of the ischiatic tuberosity (ITSTS) treated surgically. This was a multi‐institutional retrospective study. Fifty‐two dogs met the inclusion criteria, which were: histologically confirmed STS in the region of the IT treated with surgical resection between March 1st, 2009 and March 1st, 2021 with a minimum follow‐up time of 6 months. Data collected included patient signalment, preoperative diagnostics, surgical intent/method, surgical complications, histopathology, margins, outcome and cause of death. Statistical analyses were performed to determine significant factors in the treatment and prognosis of ITSTS. Overall survival time (OST) and disease progression were negatively associated with tumour grade, while recurrence was positively associated with grade and incomplete margins. Of the 52 included dogs, there were 24 grade I, 20 grade II and 7 grade III tumours. Forty dogs had reported histopathologic margins of which 26 were reported to be complete and 14 were incomplete. OST and progression‐free survival was not reached for tumours graded as I or II and was 255 and 268 days respectively, for grade III. Median time to recurrence was not reached for tumours excised with complete margins and was 398 days for those with incomplete margins. The surgical complication rate was 25%. ITSTS was not found to be a unique clinical entity in dogs as tumour behavior, treatment recommendations, and prognosis were similar to STS in other locations, with overall outcome and prognosis influenced by histologic grade and margins. While surgical complications were common, none resulted in significant morbidity or mortality.